KAJIAN AL-QUR’AN TENTANG PERAN DAN HUKUM MUSIK DALAM KEHIDUPAN ISLAMI - Fitriyani; Naurah Fachrani Saragih; Ali Akbar (PT. Saha Kreasi Indonesia, 2025)
This study examines the role of music in the life of the Muslim community from the perspective of Islamic jurisprudence, theology, and maqāṣīd al-sharī‘ah. A qualitative literature study is employed, with content analysis applied to classical and contemporary sources addressing the status of music in Islam. The main findings reveal a plurality of scholarly opinions: some view music as generally prohibited, while others permit it within specific contexts (such as social rituals, permissible entertainment, or for dawah) provided that it serves public interest, avoids fitnah, and does not impede obligatory acts of worship. The use of music in religious practice, education, and emotional expression can be seen as a vehicle for dawah, a legitimate medium for halal entertainment, and a means of emotional regulation when aligned with Shariah objectives and Islamic values. Policy implications include the formulation of guidelines that emphasize communal welfare, ethical boundaries, and contextual sensitivity to contemporary cultural dynamics while preserving core principles of faith, worship, and morality. The study recommends multidisciplinary engagement among scholars, Islamic philosophers, and practitioners in Islamic education to develop a contextualized and culturally sensitive framework for the permissibility and application of music in Islam.